TRANSFORMASI MANAJEMEN MUTU PENDIDIKAN ISLAM MELALUI PENDEKATAN SIX SIGMA: STUDI IMPLEMENTASI DI MTS RAUDLATUL FIRDAUS - Ja'far Siddik; Wahab Wahab (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2026)
This study aims to analyze the transformation of Islamic education quality management through the Six Sigma approach at MTs Raudlatul Firdaus. The novelty of the study lies in the development of an integrative model that combines the Six Sigma approach based on DMAIC (Define, Measure, Analyze, Improve, Control) with Islamic educational values, namely itqan, ihsan, and amanah. The study used a qualitative approach with a case study design. Research informants consisted of the madrasah principal, the deputy head of curriculum, and teachers involved in the implementation of the quality program. Data were collected through interviews, observations, and documentation, then analyzed thematically. The results showed that the implementation of Six Sigma encouraged a shift in quality management from an administrative approach to data-driven quality management. Through the DMAIC stages, the madrasah was able to identify quality problems, find root causes, implement improvement programs, and develop continuous evaluation mechanisms. The main findings showed that the integration of the values ​​of itqan, ihsan, and amanah strengthened the effectiveness of Six Sigma implementation in building a culture of quality, professionalism, and accountability. This study contributes to producing an adaptive, contextual, and sustainable Islamic education quality management model for the development of Islamic educational institutions.